1986
DOI: 10.2527/jas1986.632418x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in Javanese Sheep: Evidence for a Gene with Large Effect on Ovulation Rate and Litter Size1

Abstract: Three breeds of Javanese sheep are described briefly and data suggesting the segregation of a gene with large effect on ovulation rate and litter size are presented. The three breeds are Javanese Thin Tail (JTT), Javanese Fat Tail (JFT) and Semarang (SEM), the last possibly a substrain of JTT. All three breeds have mean mature ewe weights under 30 kg. Ovulation rate and litter size did not differ significantly among the three; all had litter sizes of up to 4 or 5 with a mean for mature ewes of approximately 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…Within a production or management system, the phenotypic variation of a composite trait is influenced by the level of variability among its component traits and their interactions (Snowder, 2008). Although component traits of reproduction are under the influence of many genes, a limited number of major genes associated with separate components of reproduction have been reported (Piper & Bindon, 1982;Bradford et al, 1986). Expressions of the genetic effects on reproduction are affected by numerous environmental factors such as season, climatic conditions, management, health, nutrition, breeding ratio, age and weight of doe, and libido of buck and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Within a production or management system, the phenotypic variation of a composite trait is influenced by the level of variability among its component traits and their interactions (Snowder, 2008). Although component traits of reproduction are under the influence of many genes, a limited number of major genes associated with separate components of reproduction have been reported (Piper & Bindon, 1982;Bradford et al, 1986). Expressions of the genetic effects on reproduction are affected by numerous environmental factors such as season, climatic conditions, management, health, nutrition, breeding ratio, age and weight of doe, and libido of buck and fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1982, when evidence of the first major gene for prolificacy was found by Piper and Bindon [23], and Davis et al [7] in Booroola Merinos, various authors like Hanrahan and Owen [13], Hanrahan [12], Jonmundsson and Adalsteinsson [17], Bradford et al [4], Radomska et al [26], and Davis et al [5] have suspected or demonstrated that ovulation in other sheep breeds could also result from mixed (polygenic background + major gene) inheritance. In addition, Galloway et al [11] have found the DNA mutation responsible for the Inverdale genotype shown by Davis et al [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genes in the Booroola (FecB) and Inverdale (FecX) sheep, there is evidence that major genes may be segregating in Icelandic (Johnmudsson and Adalsteinsson, 1985), Javanese (Bradford et al, 1986), Olkuska (Radomska et al, 1988), Cambridge (Owen et al, 1990;Hanrahan, 1991), Belclare (Hanrahan, 1991), Lacaune (Bodin et al, 1998) and Woodlands (Davis et al, 2001) sheep breeds. Some genes in these breeds may represent alleles for a smaller subset of genes.…”
Section: Loci Affecting Ovulation Ratementioning
confidence: 99%